Cervical Pap Smear Study and Its Utility in Cancer Screening, To Specify the Strategy for Cervical Cancer Control - Patel, Mandakini M; Pandya, Amrish N; Modi, Jigna (National Journal of Community Medicine, 2011)
The study was conducted to explore various lesions of Uterine cervix [inflammatory and growth], to find out target age group in which screening efforts can be concentrated for early detection as well as reduction of the incidence of cervical cancer, in our set up. Patients in the age group 15-50 and 50-78 years with various complaints were screened during June 2006 to December 2007. Total 995 patients were studied. Slides were fixed in 95% ethyl alcohol and stained with Pap stain. Slides were reported according to the 2001 Bethesda System, by cytopathologists. Out of 995 patients studied, 940 showed inflammation and other benign lesions. 55 patients showed premalignant and malignant lesions. Premalignant lesions were present in 30-50 year of age group.